And Still It Comes: Fate and Mortality in the Halloween Franchise - Peaty, Gwyneth (2021)
The Halloween series has gripped audiences for over 40 years. The 12th instalment, Halloween Kills (2021), is due to be released soon and promises to deliver what fans have come to expect: the return of Michael Myers from beyond the grave. One might argue that Myers is popular culture’s most famous zombie. He has been shot, burned, stabbed and decapitated, but still rises to walk on with that slow, steady gait. Relentless, he does not speak but pursues his victims with unexplained, mindless brutality. In the original 1978 film, Dr Loomis (Donald Pleasance) describes Myers as an ‘it’ not a ‘him’ – arguing that what lies behind the mask, behind the eyes, is nothing but the pure embodiment of evil; “no reason, no conscience, no understanding […] of life or death or right or wrong.” To Loomis, Myers is both more and less than a person – he is a timeless personification of death itself. “You were the first one to see it,” says Dr Wynn (Mitchell Ryan) in Halloween: The Curse of Michael Myers (1995): “You recognised its power. Evil. Pure, uncorrupted, ancient.” And yet the films repeatedly interrogate and undermine this categorisation, foregrounding the humanity of their villain even as they insist on his monstrosity.